Risk Factors and Survival Outcomes Associated with Breast Cancer Recurrence: Survival Outcomes Associated with Breast Cancer Recurrence - Gardezi, Syed Saad; Ullah, Muhammad Sami; Shakeel, Mehroosh; Shafique, Sadaf; Masood, Badar; Nisar, Bushra (Pakistan Journal of Health Sciences, 2025)
Breast cancer recurrence remains a major clinical challenge, despite advancements in diagnosis and treatment. Identifying reliable clinicopathological predictors is essential for improving long-term outcomes and guiding individualized treatment. Objective: To assess the clinicopathological characteristics and risk factors associated with breast cancer recurrence and evaluate survival outcomes in patients with operable breast cancer. Methods: This retrospective study included 281 patients diagnosed with operable primary breast cancer at a tertiary care center. Data were collected on demographic, histopathological, and treatment-related variables. Recurrence was defined as any documented local, regional, or distant relapse after initial treatment. Statistical analyses included chi-square tests for categorical variables and independent-samples t-tests for continuous variables to assess associations with recurrence. A p-value<0.05 was considered statistically significant. Results: The overall recurrence rate was 31.7 %, with distant metastasis being the most common type. Odds ratios with 95 % confidence intervals for categorical variables (molecular subtype, hormone receptor status, tumor size category, histological grade, Ki-67 index, and lymphovascular invasion) showed no statistically significant associations with recurrence. Likewise, mean differences with 95 % confidence intervals for continuous variables (age, tumor size, Ki-67 index, and disease-free survival) revealed no significant differences between recurrence and non-recurrence groups. Conclusions: No clinicopathological factor was found to be a statistically significant predictor of breast cancer recurrence in this cohort. These findings highlight the limitations of traditional pathological markers and underscore the need to integrate molecular and genomic profiling for more accurate recurrence risk assessment and personalized treatment planning.